Using the general trend equation in time series to predict the number of people infected with Covid – 19 Virus (Entrepreneurship Journal for Finance and Business, 2022)
The increase in the number of people infected with the virus around the world and the human and material losses caused by this phenomenon and the social and psychological effects it generates include all categories of society. The main purpose of studying this virus is to know ways to reduce losses and make future predictions about it.In this research, time series (general trend equations) were used in the theoretical side and monthly data analysis on the virus (covid 19) and for the time period (2019-2020) because of the high accuracy and flexibility of these equations in analyzing the time series.The results showed that the appropriate and efficient model is the quadratic model to represent the time series according to the comparison with other models.